LCA analysis as a tool to assess the impact of electricity production on the environment = Analiza LCA jako narzędzie służące do oceny wpływu produkcji energii elektrycznej na środowisko - Dzikuć, Maciej; Piwowar, Arkadiusz (Zielona Góra: Faculty of Economics and Management Press)
The paper presents a method for Life Cycle Assessment LCA (Life Cycle Assessment) to evaluate the ecological characteristics of products, presents a procedure for the implementation of the LCA with an overview of the various stages. Moreover the validity of using this method to evaluate the energy sector. The article also points to the directions of the Polish energy sector and pointed to the need to determine the environmental risks associated with the production of energy. Energy industry in Poland, the structure of energy production requires special supervision. The use of coal and lignite as a primary fuel results in significant the environmental impact.
Keywords: Ocena Cyklu Życia (LCA); ekologia; energia; Life Cycle Assessment; ecology; energy